Cooperation and subcontracting enterprises as a form of deepening the process of integration within the Eurasian Economic Union - A. A. Urunov; I. M. Morozova (Управление)
The article considers such forms of integration between enterprises as subcontracting and cooperation, designed to increase the industrial potential, activate the processes of restructuring industries and move them to a qualitatively new level. The purpose of the study is to identify the features and trends of the process of integration of enterprises through the mechanism of subcontracting and cooperation within the Eurasian Economic Union (EAEU) and to substantiate the prospects for its further development.The paper describes the degree of development of national subcontracting markets in the countries that are part of the Eurasian Economic Union, and identifies the features of national systems for supporting cooperation and subcontracting processes. The authors carry out the analysis of the dynamics of cooperative supplies between the EAEU member states in the sectoral context, as well as the analysis of structural shifts in trade in intermediate goods in the context of the participating countries. The latter found a shift in the final links of the cooperative chains of product value formation in the EAEU space, which indicates the deepening of integration processes. The article considers the problems of information, financial and regulatory support for the development of subcontracting and cooperation. The paper determines the reasons that hinder the integration processes in the EAEU. The results of the study can be used in the development of an industrial strategy and integration policy in the Eurasian space.